Os técnicos em assuntos educacionais do Instituto Federal do Paraná: em busca de sua identidade profissional. - Lewandowski, Jacqueline Maria Duarte (2018)
This dissertation aims to contribute with the Professional Identity of the federal public servant occupying the position of Technical in Educational Affairs of the Federal Institute of Paraná. Wecarry out the historical and political contextualization that the Professional and Technological Education (EPT) has passed in recent years, until the creation of the Federal Institutes of Education, Science and Technology to understand the context and the daily activities of the Technicians in Educational Affairs, in order to contribute to the formation of Professional Identity and guide the practice of these professionals. This position is part of the career of Administrative Technicians in Education, Career Plan (PCCTAE) Law n. 11.091 2005 and is intended exclusively for federal education al institutions, in order to support the educational process, contributing to the development of teaching, research and extension activities. In order to achieve the objective of this dissertation, a bibliographical and Technicians in Educational Aff airs and elaboration of analyzes from literature review and the legislation in force on the subject. Questionnaires were applied to the 46 IFPR Educational Technical Officers, and we obtained 32 responses, totaling a 69.5% rate of return.